Global Accumulation and the New Middle East Wars - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2002)
The unravelling of the Middle-East peace process continues to baffle the pundits. The early optimism of the Oslo peace accord has now turned into despair. Prime minister Rabin was assassinated by a Jewish extremist. The Palestinians have embarked on a new Intifada. And Israel has re-occupied much of the West Bank. What brought this reversal? How deep are the fractures? Can they be healed?.
Keywords: 330; arms; accumulation; capital; centralization; conflict; crisis; distribution; dual economy; elite; energy; finance; globalization; growth; imperialism; distribution; Israel; Middle East; military; security; oil; OPEC; peace; politics; power; privatization